Cerebrotendinous xanthomatosis: a comprehensive review of pathogenesis, clinical manifestations, diagnosis, and management - Nie, Shuke (Orphanet J Rare Dis, 2014)
Cerebrotendinous xanthomatosis (CTX) OMIM#213700 is a rare autosomal-recessive lipid storage disease caused by mutations in the CYP27A1 gene; this gene codes for the mitochondrial enzyme sterol 27-hydroxylase, which is involved in bile acid synthesis. The CYP27A1 gene is located on chromosome 2q33-qter and contains nine exons. A CYP27A1 mutation leads to decreased synthesis of bile acid, excess production of cholestanol, and consequent accumulation of cholestanol in tissues. Currently there is no consensus on the prevalence of CTX, one estimate being <5/100,000 worldwide. The prevalence of CTX due to the CYP27A1 mutation R362C alone is approximately 1/50,000 in Caucasians. Patients with CTX have an average age of 35 years at the time of diagnosis and a diagnostic delay of 16 years. Clinical signs and symptoms include adult-onset progressive neurological dysfunction (i.e., ataxia, dystonia, dementia, epilepsy, psychiatric disorders,peripheral neuropathy, and myopathy) and premature non-neurologic manifestations (i.e., tendon xanthomas, childhood-onset cataracts, infantile-onset diarrhea, premature atherosclerosis, osteoporosis, and respiratory insufficiency). Juvenile cataracts, progressive neurologic dysfunction, and mild pulmonary insufficiency are unique symptoms that distinguish CTX from other lipid storage disorders including familial dysbetalipoproteinemia, homozygous familial hypercholesterolemia, and sitosterolemia, all of which might also present with xanthomas and cardiovascular diseases. Brain magnetic resonance imaging (MRI) shows bilateral lesions in the dentate nucleus of the cerebellum and mild white matter lesions. The classical symptoms and signs, namely elevated levels of cholestanol and bile alcohols in serum and urine, brain MRI, and the mutation in the CYP27A1 gene confirm the diagnosis of CTX. Early diagnosis and long-term treatment with chenodeoxycholic acid (750 mg/d) improve neurological symptoms and contribute to a better prognosis.